2008
DOI: 10.1007/s00284-008-9289-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Stress in C. jejuni Inactivation During Freeze-Thaw Treatment

Abstract: Campylobacter jejuni represents one of the leading causes of bacterial enteritis throughout the world. Poultry is an important source of C. jejuni. Despite hygiene measures taken in the production chain, C. jejuni is frequently isolated from poultry meat. C. jejuni is a microaerophilic pathogen, affected by oxidative stress. Freeze-thaw treatment induces cell death by several mechanisms, including oxidative stress. In this article, we investigate the role of oxidative stress in C. jejuni sensitivity during and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…In contrast, at higher temperatures (at 42 or 52°C), no viable C. coli cells were detected after 24 h using either bacterial culture or RT-qPCR method. These findings are in agreement with data from previous study reported by Garénaux et al (2009) who revealed that a cross protection between the cold shock response and oxidative stress response might explain the increased resistance of bacteria at low temperature. In addition, it has been shown that superoxide dismutase, as well as other oxidized stress related proteins were over-expressed at 4°C (Stintzi, 2003).…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, at higher temperatures (at 42 or 52°C), no viable C. coli cells were detected after 24 h using either bacterial culture or RT-qPCR method. These findings are in agreement with data from previous study reported by Garénaux et al (2009) who revealed that a cross protection between the cold shock response and oxidative stress response might explain the increased resistance of bacteria at low temperature. In addition, it has been shown that superoxide dismutase, as well as other oxidized stress related proteins were over-expressed at 4°C (Stintzi, 2003).…”
Section: Discussionsupporting
confidence: 94%
“…For instance, in Campylobacter superoxide dismutase (SOD) was found to play an important role in cryotolerance (18,35), as well as in the survival in macrophages (29) and in the colonization of chickens (31). In L. monocytogenes, SOD is required for virulence in the murine model and is controlled posttranslationally by phosphorylation (1).…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacter is probably also inactivated by an oxidative burst when high pressure treatment is applied [16]. Moreover, oxidative stress and redox-related proteins were found to be over-expressed in C. jejuni stressed with paraquat, a strong oxidizing agent [17].…”
Section: Introductionmentioning
confidence: 99%